ETIMON PAN *MANUK ‘AYAM’ DALAM DUNIA KE-SIAP-AN DI BALI - Dwi Mahendra Putra; I Putu Permana Mahardika; Ni Made Ari Dwijayanthi (WIDYANATYA, 2021)
This research describes the ecology of etymon PAN *manuk in Balinese based on the theory of Historical Linguistics Comparative and Ecolinguistics. This research is to obtain a comprehensive inheriting of etimon PAN *manuk in the world of siap in Balinese culture. The data was taken from Balinese spoken and Proto-Austronesia languages. The data collected by direct observation and combined with note-taking. The collected data was analyzed by applying the theory of Historical Linguistics Comparative and Ecolinguistics. The results of this study indicates that etymon PAN *manuk creating forms of synonymous and compositing creations in order to remain inherited. Based on the analysis conducted, it was found that the etymon *manuk reflecting the interaction of Balinese speakers with siap 'chicken' lexicon that has the same meaning field as etymon PAN *manuk.